2014
DOI: 10.1002/2014gl061800
|View full text |Cite
|
Sign up to set email alerts
|

Predicting flow and transport in highly heterogeneous alluvial aquifers

Abstract: Successful prediction of groundwater flow and solute transport through highly heterogeneous aquifers has remained elusive due to the limitations of methods to characterize hydraulic conductivity (K) and generate realistic stochastic fields from such data. As a result, many studies have suggested that the classical advective-dispersive equation (ADE) cannot reproduce such transport behavior. Here we demonstrate that when high-resolution K data are used with a fractal stochastic method that produces K fields wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…This skewness value not only qualitatively agrees with the anomalous transport conditions observed at this site, it also suggests that such conditions may be mainly the effect of the low geological entropy of the aquifer. This is consistent with the presence of connected structures and organized features as suggested by several previous studies [ Dogan et al ., ; Bianchi and Zheng , ; Zheng et al ., , and references therein].…”
Section: Results and Analysismentioning
confidence: 98%
“…This skewness value not only qualitatively agrees with the anomalous transport conditions observed at this site, it also suggests that such conditions may be mainly the effect of the low geological entropy of the aquifer. This is consistent with the presence of connected structures and organized features as suggested by several previous studies [ Dogan et al ., ; Bianchi and Zheng , ; Zheng et al ., , and references therein].…”
Section: Results and Analysismentioning
confidence: 98%
“…Dogan et al . [] demonstrated that the classical ADE with lab‐scale dispersivity can successfully match the tracer behavior at MADE if the fine‐scale variability of the hydraulic conductivity field is mapped out. These findings strengthen the conclusion of section 3.2 and the general ones of the Appendix : transport is aquifer‐specific and prediction requires characterization and modeling pertinent to the particular structure.…”
Section: Analysis Of Scale Dependence Of Macrodispersivity Datamentioning
confidence: 99%
“…Natural systems should not be constrained by this limit, and macrodispersive conditions may also exist for highly heterogeneous systems, even in the absence of stochastic theories. Dogan et al (2014) demonstrate that when highresolution hydraulic conductivity (K ) data are used with a fractal stochastic method that produces K fields with adequate connectivity, the classical ADE can accurately predict solute transport at the MADE site. The authors use data from a novel direct-push (DP) methodology and flowmeter logging coupled with fractal interpolation conditioned to the measured K data to show how the limitation of inadequate aquifer characterization data can be overcome.…”
Section: Strongly Heterogeneous Systems: the Made Sitementioning
confidence: 99%